Concomitant initiation of combination therapy with macitentan and tadalafil in pulmonary arterial hypertension (PAH) patients with comorbidities: real-world data from OPUS and OrPHeUS. (3rd October 2022) - Channick, R; Chin, K M; Kim, N H; Ong, R; Turricchia, S; Mitchell, L; McLaughlin, V V
Abstract: Background: Guidelines for the management of pulmonary arterial hypertension (PAH) recommend early combination therapy of an endothelial receptor antagonist (ERA) and a phosphodiesterase type-5 inhibitor (PDE5i) [1]. There is, however, limited guidance about the management of PAH patients with comorbidities. Purpose: To describe the demographics, clinical characteristics, safety, tolerability, and outcomes associated with initiation of the ERA macitentan and the PDE5i tadalafil in patients with comorbidities in the US OPsumit® USers (OPUS) and the OPsumit® Historical USers cohort (OrPHeUS) combined dataset. Methods: This analysis reports data from the OPUS registry (Apr 2014–Jun 2020) and OrPHeUS medical chart review (Oct 2013–Mar 2017) on PAH patients initiating macitentan and tadalafil (M+T) combination therapy, in any order, as concomitant initiation (≤60 days apart, concomitant initiation group). The index date was defined as the start date of the second therapy (i.e., the start of combination therapy). Patients were further grouped by the number of comorbidities present prior to or at macitentan initiation: systemic hypertension, diabetes, renal insufficiency, BMI ≥30 kg/m 2, other signs of right heart failure and atrial fibrillation. Results are presented descriptively alongside results for all PAH patients receiving M+T combination therapy (overall M+T group). Results: Of the 1336 PAH patients that received M+T combination therapy, 431 (32%) were in the concomitant initiation group. In the concomitant initiation and overall M+T groups, respectively: 72% and 68% had ≥1 comorbidity, and the most common were systemic hypertension (47% and 47%), obesity (32% and 26%) and diabetes (23% and 22%). Patients were more likely to be older, male and have idiopathic/heritable PAH with increasing comorbidity burden (Table 1). Patients in the concomitant initiation group were more likely to be incident (median time from diagnosis: 1–2 months vs 9–24 months in the overall M+T group; Table 1). Most patients had ≥1 adverse event (AE); in both groups, patients with a high comorbidity burden (≥3) were more likely to have had an AE and to have discontinued treatment (Table 2). The incidence rate of first all-cause hospitalisation and mortality by comorbidity was comparable between the concomitant initiation and overall M+T groups. Conclusions: In the real-world, concomitant initiation of M+T is used in PAH patients with comorbidities, usually shortly after diagnosis. Patient characteristics were similar for the concomitant initiation and overall M+T groups, with the exception of time from diagnosis. At index date, age, gender proportion, and PAH aetiology differed between the comorbidity groups. The safety profile of M+T combination therapy in the concomitant initiation group was consistent with that in the overall M+T group. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Actelion Pharmaceuticals Ltd, a Janssen Pharmaceutical Company of Johnson & Johnson